2017
DOI: 10.1002/app.45777
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polycarbonate/poly(acrylonitrile‐butadiene‐styrene)/mesoporous silica nanocomposite films and its rheological, mechanical, and sound absorption properties

Abstract: The homogeneous polycarbonate/poly(acrylonitrile-butadiene-styrene) (PC/ABS) nanocomposite thin films were prepared by a facile solvent casting method using phenylene modified-mesoporous silica materials as additives and dichloromethane as a solvent. The physicochemical analyses using small-angle X-ray scattering, nitrogen adsorption-desorption, solid-state 13 C and 29 Si nuclear magnetic resonance, and scanning electron microscope were investigated to provide clear physical and chemical properties for modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In previous studies, the simple combinations of polymers and fillers such as mica powder [41], graphene foam [42], and mesoporous silica [43] could not significantly increase the sound absorption of materials at low frequency. In particular, the SAC was hard to increase at a frequency below 1000 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the simple combinations of polymers and fillers such as mica powder [41], graphene foam [42], and mesoporous silica [43] could not significantly increase the sound absorption of materials at low frequency. In particular, the SAC was hard to increase at a frequency below 1000 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Nanocomposites containing mesoporous materials can be used as sound insulation carriers. Furthermore, the external mesopores also contribute to the sound transmission loss 16 . Huq et al systematically studied the sound insulation properties of microporous activated carbon (AC) and mesoporous carbon nanotubes (CNTs) in a polymer matrix (polyvinyl acetate, PVA).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the external mesopores also contribute to the sound transmission loss. 16 Huq et al systematically studied the sound insulation properties of microporous activated carbon (AC) and mesoporous carbon nanotubes (CNTs) in a polymer matrix (polyvinyl acetate, PVA). Mesopore is the most important component to improve the sound insulation effectiveness.…”
mentioning
confidence: 99%
“…The study confirmed that lattice structures can absorb sound mostly above 1 kHz. Sim et al [9] were involved in the preparation of nanocomposite films of polycarbonate/polyacrylonitrile-butadiene-styrene (PC/ABS), and investigated not only the rheological and mechanical properties of this material, but also its ability to absorb sound. The PC/ABS thin films were made by a simple solvent casting method using phenylene modified-mesoporous silica materials as additives and dichloromethane as a solvent.…”
Section: Introductionmentioning
confidence: 99%